1986
DOI: 10.1007/bf01849224
|View full text |Cite
|
Sign up to set email alerts
|

IUD insertion at cesarean section — the Chinese experience

Abstract: This review reports the experience of nine studies in Chinese maternity hospitals with insertions of an intrauterine device (IUD) at the time of cesarean section. In contrast to the usually high expulsion rates associated with immediate postpartum vaginal insertions, all nine studies reported low expulsion rates, thus resulting in high continuation rates with this procedure, comparable to those with interval insertions. This immediate post-cesarean section insertion procedure was also found to be safe. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Similar results were seen by Beltagy et al, Eroglu et al, Celen et al (Table 11). 12,13 Our results are in accordance with studies by Siemens et al and Zhou S et al There were 97.5% (n=38) and 2.5% (n=1) expulsions in vaginal and intra cesarean insertions respectively.…”
Section: Iud Expulsionsupporting
confidence: 92%
“…Similar results were seen by Beltagy et al, Eroglu et al, Celen et al (Table 11). 12,13 Our results are in accordance with studies by Siemens et al and Zhou S et al There were 97.5% (n=38) and 2.5% (n=1) expulsions in vaginal and intra cesarean insertions respectively.…”
Section: Iud Expulsionsupporting
confidence: 92%
“…On the other hand, inverted or obliquely placed IUCDs were found to be associated with maximum number of the side effects and it should be followed up stringently. Rate of malposition seen was more after normal vaginal delivery than the intra c-section placement of the IUCDs [30 (68.2 %) vs. 14 (31.8 %); p value \ 0.0001], which is comparable with the studies done previously [12][13][14][15] No statistically significant difference was seen with regard to the method of insertion (Kelly vs. manual) [p value 0.5] [16]. The most common complaint among the IUCD users in the study population was of menstrual irregularity (27.71 %) followed by pain in lower abdomen (20.65 %), expulsion (9.78 %), and vaginal discharge (7.60 %).…”
Section: Discussionsupporting
confidence: 85%
“…Since IUD insertion during C-section was proposed by Zerzavy in 1967 [23], low expulsion rates (fewer than 10 per 100 women at 12 months of use) have been reported in clinical trials conducted in Mexico, China and Belgium [24][25][26][27][28]. This is significant, because despite different patient characteristics, clinic practices, and varying types of IUDs, IPPI after C-section across various studies has shown consistently low expulsion rates.…”
Section: Ippi During Cesarean Section (C-section) Deliverymentioning
confidence: 99%